Thermoanalytical and Antimicrobial Studies of o-Amino-N,N-dipropylbenzylamine Complexes With Cobalt(II), Nickel(II) and Iron(II) - Mazher, Farhana; Khan, Bushra (Asian Journal of Chemistry, 2010)
o-Amino-N,N-dipropylbenzylamine complexes with Co(II), Ni(II) and Fe(II) are reported. Evaluation of the nature of complexes has been carried out on the basis of spectroscopic and analytical techniques. Thermal behaviour of the complexes has been studied by the thermogravimetric and differential thermal analysis. Antimicrobial activity of o-amino-N,Ndipropylbenzylamine and its metal complexes are reported against some pathogenic bacteria and fungi by diffusion plate method.